THE CHINESE PATH – MODERNIZATION TRANSFORMATION OF THE CHINESE CIVILIZATION - Sun Lei (Сравнительная политика, 2019)
The article deals with “Chinese path” ‒ modernization transformation of the Chinese Civilization. It is shown that “Chinese path” reflects the formation and development of a new configuration of Chinese civilization. From civilizational transformation to “the Chinese path” is the gradual historical development, was the failure “to improve the state of construction of the” victory “of the revolution state-building”, the success of the “economic state-building”, constructing a “civilizational state-building”. Socialism with Chinese characteristics liberates and develops the productive forces, creating a socialist market economy, socialist democracy, advanced socialist culture, harmonious socialist society, eco-culture of socialism.